Discovering the secrets of leadership success: Comparing commercial and academic preoccupations. Issue 1 (February 2022) - Maskor, Mazlan; Steffens, Niklas K; Peters, Kim; Haslam, S Alexander
Having access to the "secrets" of leadership promises to be immensely valuable to those wishing to lead. But what are these "secrets"? In this study, we examined the types of non-academic theorizing (communicated as leadership "secrets") that writings for a general audience convey. A content analysis of 131 commercial books on leadership "secrets" revealed seven major "secrets" that pertained to (1) knowledge and learning, (2) habits, behaviors, and practices, (3) handling failure, challenges, and struggle, (4) personal inspiration, drive, and motivation, (5) team, group, and organizational strategy, (6) choices and decisions, and (7) communication skills. Intriguingly, the prevalence of leadership "secrets" varied in a cyclical pattern across time such that some "secrets" lost prominence in one period only to reemerge in another. We also observed a considerable degree of correspondence between the foci of topics in these commercial outlets and the foci of academic publications. JEL Classification:J24, O15, M12